Animal diversity declines with broad-scale homogenization of canopy cover in African savannas. (October 2018) - McCleery, Robert; Monadjem, Ara; Baiser, Benjamin; Fletcher, Robert; Vickers, Karen; Kruger, Laurence
Abstract: Savannas are increasingly threatened by anthropogenic forces that are causing broad-scale directional shifts in woody vegetation that homogenizes their structure. Yet, whether animal communities respond consistently to changes in woody vegetation in savannas, particularly in terms of the effects of spatial scale, remains poorly understood. We addressed this gap by testing for changes in birds, bats and terrestrial small mammals across a gradient of woody cover in the savannas of southeastern Africa for two years at multiple spatial scales. We found that homogenization of vegetation structure corresponded with decreases in animal richness, diversity and functional diversity. Additionally, metrics of animal diversity declined at opposing ends of a canopy cover gradient (<10% and >65%), where we found distinctly different animal assemblages. These patterns were consistently more pronounced on a broader grid scale (30.25 ha) when compared with the plot scale (0.25 ha). The broad-scale reductions in the diversity and functions of animals observed may be indicative of reductions in the resilience, stability and ecosystem function of tropical savannas. Our results suggest that conservation and management aimed at promoting heterogeneity at broad scales may be critical for maintaining diversity and functionality in savannas. Highlights: Animal diversity was positively associated with vegetation heterogeneity. Diversity declined at opposing ends of the canopy cover (<10% or >65%) gradient. Animal diversity began to decrease with canopy cover between 41% and 51%. Patterns of animal diversity were more pronounced on broader scales. High and low canopy cover savannas had distinctly different assemblages of animals.